DMAIC for process digitalization: a hospital case study - Ramires, F. S. (2020)
Purpose - This paper presents how to implement the DMAIC cycle as an element to X-ray the progress of a digitalization initiative focused on the ambulance's request system for daily transport of patients initiated in a Portuguese hospital, which was not achieving the expected results. The research has the goal of not only contributing to the literature on the application of the Lean Six Sigma methodology to healthcare operations but also, of giving practical recommendations on how managers can leverage on the same approach, and apply the concept in their internal process improvement initiatives to reduce friction in digitalized processes. Ultimately, it is shown how a methodology like DMAIC, presents in itself a great option to start and methodically lead a business process digitalization project. Methodology - The authors chose to follow an Action Research methodology while approaching the problem at stake with the DMAIC framework. Findings - DMAIC can be a relevant problem-solving structure to measure the success and support the digitalization of business processes. Originality - The originality of this paper lies in the application of a logical structure such as the DMAIC cycle to analyze the quality issues inherent to the digital version of an ambulance's request system. Practical implications - This case study depicts how the operationalization of digitalization initiatives using the DMAIC framework can be more effective while allowing organizations to adequately and actively react to the implementation problems. It presents improvements of 23% lower lead times for a redesigned digitalized ambulance's request system.